POST-QUANTUM CRYPTOGRAPHY: CHALLENGES AND PROSPECTS FOR DEVELOPING QUANTUM-STABLE ALGORITHMS TO ENSURING THE SECURITY OF INFORMATION SYSTEMS - PETRUSHKO, IRYNA; POLISHCHUK, VOLODYMYR; MATEI, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The development of quantum computers is one of the most significant technological developments of our time, opening new horizons in computing capabilities. However, it also poses serious threats to existing cryptographic algorithms, which are the basis of the security of modern information systems. The paper presents the results of research on post-quantum cryptography and its role in ensuring information security in the context of the development of quantum computers. The purpose of this paper is to compare modern post-quantum, i.e., quantum-stable cryptographic algorithms, assess their applicability for different classes of tasks, and predict the development paths of cryptographic methods for information protection. To achieve this goal, methods of comparative analysis and mathematical modeling are used, which allow for assessing the effectiveness and security of algorithms in different conditions. The study results show that post-quantum algorithms provide reliable information protection in the context of potential quantum attacks while maintaining a high-efficiency level. The conclusions emphasize the need to adapt existing cryptographic systems to new security requirements, particularly through integrating post-quantum algorithms into cloud services and blockchain technologies. The research results can be used to improve data protection mechanisms in information systems and to develop new cryptographic standards in the era of quantum computing. Therefore, plans for future research are outlined, namely: the effectiveness of implementing post-quantum algorithms in various industries, including finance, medicine, and government, will be analyzed; methods for optimizing cryptographic systems will be developed to ensure a balance between security and performance; new mathematical approaches will be studied that can be used to create quantum-resistant algorithms.